Benefits and Drawbacks of Smartphone Use on English Academic Performance of Grade 3 Learners - Guerrero, Jonna May; Espiritu, Raymond D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study considered the two pathways through which smartphone use is associated with third-grade English students’ academic performance. Descriptive-correlation research design was used in the study with the help of a survey questions and testing as main tools for data collection. A total of 46 participants were included in this study, who participated during School Year 2024 – 2025. Descriptive statistics and inferential statistics were mean, standard deviation, ANOVA and Pearson Correlation. KULLY The demographic results of the study were higher percentages of respondents aged 8. The majority of the respondents are male. The respondents have agreed on the positive role of using smartphones in academic achievement in English (listening and speaking skills, reading and writing skills). The respondents concur that there are disadvantages of using smartphones on academic performance in English as far as listening skills, speaking skills reading skills and writing skill is concerned. The academic achievement of the respondents is highly commendable. There are notable difference in facilitation of smartphones when classified based on gender and age In listening skill, In speaking skills, In reading skill, writing skills. It is suggested in the study that Introduce interactive stories, rhymes and songs available through educational apps and audiobooks. This can supplement vocabulary and listening skills. Limit screen time and have students retell or summarize what they hear in listening exercises to make the work more interactive. Set clear limits on screen time, so that kids don’t abuse their smartphones.